Optimization of Extraction Parameters for Phenolics Recovery from Avocado Peels Using Ultrasound and Microwave Technologies - Lorena Martínez-Zamora; María Carmen Bueso; Mathieu Kessler; Rosa Zapata; Perla A. Gómez; Francisco Artés-Hernández (Foods)
Background: Avocado (Persea americana) peels account for ~20% of the fruit weight and are rich in bioactive compounds, offering significant revalorization potential. This study optimized the extraction parameters of phenolics using ultrasound- (UAE) and microwave-assisted technologies (MAE) with a Central Composite Design (CCD). Methods: The extraction variables included EtOH concentration (0–100%), temperature (13–47 °C for UAE and 55–95 °C for MAE), and time (3–37 min for UAE and 3–27 min for MAE). Total antioxidant capacity (TAC) and total phenolic compounds (TPC) were measured, while individual phenolics were analyzed via HPLC/MS. Results: EtOH concentration was the most influential variable, with optimal conditions involving 94.55% EtOH and moderate temperatures over short times (45 °C for 5 min in UAE and 67 °C for 12 min in MAE). Both techniques yielded comparable results for effective conditions, though MAE required higher temperatures and longer times. In this sense, the data show that UAE extracted higher concentrations of procyanidins (+15%), demonstrating superior performance using a lower time and temperature, making it more efficient. Conclusions: UAE and MAE effectively extract antioxidants, promoting sustainability in the agri-food sector.